Entertainment computing -- ICEC 2017 : 16th IFIP TC 14 International Conference, Tsukuba City, Japan, September 18-21, 2017, Proceedings /: 16th IFIP TC 14 International Conference, Tsukuba City, Japan, September 18-21, 2017, Proceedings. (2017) - Unknown
No abstract available